Difference in DNA-binding abilities of Fur-homolog DNA binding protein from Neisseria gonorrhoeae. (October 2016) - Bagchi, Angshuman
Abstract: Gonorrhea is a severe disease infecting both men and women worldwide. The causative agent of the disease is Neisseria gonorrhoeae . The organism mostly affects human beings in iron restricted environments. In such an environment the organism produces a set of proteins which are mostly absent in iron rich environments. The expressions of the genes for the proteins are regulated by the transcription factor (TF) belonging to the Fur family. Interestingly, the same TF acts as the activator and repressor of genes. In this present work, an attempt has been made to analyze the molecular details of the differential DNA-binding activities of the TF from Neisseria gonorrhoeae to come up with a plausible molecular reason behind the difference DNA binding activities of the same TF. Computational modelling technique was used to build the three dimensional structure of the TF. Molecular docking and molecular dynamics simulations were employed to determine the binding interactions between the TF and the promoter DNA. With the help of the computational techniques, the biochemical reason behind the different modes of DNA binding by the TF was analyzed. Results from this analysis may be useful to future drug development endeavours to curtail the spread of Gonorrhea. Highlights: DNA-binding abilities of Fur-homolog. Molecular Dynamics Simulations. DNA-Protein Interactions. Biomolecular Mechanisms.